1992
DOI: 10.1128/aac.36.12.2804
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and tissue penetration of a single dose of ceftriaxone (1,000 milligrams intravenously) for antibiotic prophylaxis in thoracic surgery

Abstract: The pharmacokinetics and tissue penetration of ceftiaxone after a single intravenous injection of 1,000 mg to 17 patients for antibiotic prophylaxis in thoracic surgery were studied. The patients were scheduled for elective noncardiac thoracic surgery. Adequate levels in serum (higher than Noncardiac thoracic surgery is "contaminated-aseptic surgery" in most cases (4,6,7,11). Antibiotic prophylaxis is used against pathogens most likely to contaminate the surgical wound: Escherichia coli, various members of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 19 publications
3
11
0
Order By: Relevance
“…In 1961, Burke [43] showed the timing of SAP to be crucial in animals. Subsequent studies in humans suggested that adequate tissue levels of an appropriate antibiotic during surgery were essential [21,[44][45][46][47].…”
Section: When To Administer Surgical Antimicrobial Prophylaxis?mentioning
confidence: 99%
“…In 1961, Burke [43] showed the timing of SAP to be crucial in animals. Subsequent studies in humans suggested that adequate tissue levels of an appropriate antibiotic during surgery were essential [21,[44][45][46][47].…”
Section: When To Administer Surgical Antimicrobial Prophylaxis?mentioning
confidence: 99%
“…The highest ELF concentrations were achieved 1 hour after infusion (4.06 ± 6.64 mg/L), and the highest mean level of ELF penetration was 9.40% 5 hours after infusion. However, in comparison to ceftriaxone, another antimicrobial drug used frequently for treatment of CAP, ertapenem concentrations in lung tissue were much lower (7.60 ± 4.85 mg/kg vs 27.0 ± 9.00 mg/kg) 26 . Unfortunately, in the available literature, no data are present for penetration of ceftriaxone into ELF.…”
Section: Discussionmentioning
confidence: 90%
“…However, in comparison to ceftriaxone, another antimicrobial drug used frequently for treatment of CAP, ertapenem concentrations in lung tissue were much lower (7.60 ± 4.85 mg/kg vs 27.0 ± 9.00 mg/kg). 26 Unfortunately, in the available literature, no data are present for penetration of ceftriaxone into ELF. Like other βlactam antibiotics, the penetration of ertapenem into alveolar cells was poor.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Because of this, lower concentrations of antibiotic in the blood and other tissues occur. 15,16 Surgery for patients who are obese also is technically challenging and creation of dead space (ie, an actual or potential cavity remaining after the closure of an incision that is not obliterated by operative technique) regularly occurs. Finally, typical doses of antimicrobial prophylaxis are not adequate to "fill up the tank" in patients who are obese because the volume of distribution is larger.…”
Section: Weight-based Dosing Of Perioperative Antibioticsmentioning
confidence: 99%